Indicadores antropométricos, bioquímicos e atividade física de escolares do ensino fundamental do município de Cruzeiro do Oeste - PR - Oliveira, Ana Paula de (2011)
Obesity is an epidemic disease that increases worldwide. Childhood obesity is now considered a public health problem, it occurs by multiple factors, mainly due to lifestyle. The study investigated the association between anthropometric indices of body fat distribution, blood pressure and dietary habits, physical activity and lipid profile of schoolchildren of both sexes, aged between 6 and 10 years of municipal schools in Cruise West / PR. A descriptive epidemiological and diagnostic was conducted on a population of 1074 schoolchildren. The evaluation consisted of measurements of waist circumference (WC) and Body Mass Index (BMI) for the classification of nutritional status by sex and age cutoff points proposed by Cole. Questionnaire socioeconomic level, physical activity questionnaire and food frequency were evaluated. We also evaluated the blood pressure (BP) used as a reference The Fourth Report on the Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents. To evaluate the lipid profile were used cutoff points recommended by the I Guidelines for the Prevention of Atherosclerosis in Childhood and Adolescence of the Brazilian Society of Cardiology. Data analysis used the following tests: Shapiro-Wilk, Mann- Whitney, one-way ANOVA, post hoc Bonferroni and Games-Howell, Chi-square and Fischer. The significance was 5% (p <0.05). Classification of Body Mass Index was 16.6% overweight and 9.8% obese. For waist circumference 68.6% and 31.4% as desirable as amended. There is change in waist circumference was increased in proportion to age groups. The results of blood pressure have 26.4% of students with measures hypertensive and 11.8% are in the borderline range. Only 54.1% of students did not show any change in BMI and WC and BP. The coach was not associated with nutritional status of schoolchildren. The classification of the lipid profile of the sample indicates that 23% had total cholesterol (TC) and increased 36.3% borderline, 2.2% are Low Density Lipoproteins (LDL-c) increased and 23% borderline, 3% had Triglycerides (TG) and increased 4.4% borderline, and glucose (GL) showed no increase. The appropriate group showed the highest value of total cholesterol (64.5%). For the LDL-c were 33.3% for appropriate overweight or obese and the TG, the schoolchildren were overweight and obese were unaffected. The study results show changes in anthropometric measurements, blood pressure and lipid profiles and associations with physical inactivity and poor eating habits. Childhood obesity is a serious public health problem, which grows in the Brazilian population in every social level, characterized by a context of worldwide epidemic.